A colorimetric biosensor for ultrasensitive detection of the SURF1 gene based on a dual DNA-induced cascade hybridization reaction. Issue 40 (27th September 2021) - Yu, Tianxiao; Wang, Yafang; Quan, Huili; Meng, Yucui; Wang, Zhaohua; Zhao, Chunchao; Guo, Qing; Ge, Jun
Abstract : In this work, a simple and ultrasensitive colorimetric biosensor for detection of SURF1 gene fragments (Leigh syndrome) has been developed based on a dual DNA-induced cascade hybridization reaction. Abstract : In this work, a simple and ultrasensitive colorimetric biosensor for detection of SURF1 gene fragments (Leigh syndrome) has been developed based on a dual DNA-induced cascade hybridization reaction. Firstly, a biotin labeled capture probe was immobilized on a streptavidin labeled 96-well transparent plate surface. Then the target SURF1 fragment and auxiliary probe S1 were added into the reaction system to form a "Y" structure with the capture probe. Furthermore, to achieve a highly efficient signal amplification strategy, digoxin labeled P1, P2, P3 and P4 probes were used to cause a dual DNA-induced cascade hybridization reaction on the "Y" structure of the 96-well plate surface. As a detection probe, the HRP anti-digoxin antibody was combined on the surface to produce a colorimetric response to the SURF1 fragment in the presence of TMB. Under the optimal conditions, the established method exhibited a wide linear range from 1.0 × 10 −13 M to 1.0 × 10 −8 M and a detection limit to SURF1 as low as 1.73 × 10 −14 M. In addition, the strategy has been successfully applied to the detection of SURF1 in spiked human serum samples. Therefore, the established biosensor has potential application prospects in gene fragment analysis and early diagnosis of clinical diseases.